Normal versus half-normal saline in the treatment of children with diabetic ketoacidosis - Sally R Eid; Amal G Mohamed; Nada M F. ElSayed; Raya A M. Saleh (Journal of Medicine in Scientific Research, 2021)
Objective This study aims to determine the effect of 0.9% saline (NS) versus 0.45% saline (half NS) on blood pressure and serum electrolytes in children with diabetic ketoacidosis. Patients and methods This is a cross-sectional prospective comparative study carried out on 105 patients (1–18 years) from those admitted to the pediatric ICU of Al-Zahraa University Hospital from March 2017 to August 2019. Cases were divided into three groups (35 in each group). Group I patients received a shock, deficit, and maintenance therapy with NS. Group II patients received a shock therapy NS along with deficit and maintenance therapy with half NS. Group III patients received a shock, deficit, and maintenance therapy with half NS. Results There were no hypotensive cases among all patients. There was a significant decrease in mean arterial blood pressure in the three groups after treatment. There was a significant increase in serum corrected sodium level in group I after treatment, whereas there was a significant decrease in its level in groups II and III. Serum potassium level showed an insignificant decrease after treatment in all groups. Blood glucose level significantly decreased after treatment in the same group, but in comparison with other groups, the differences were insignificant. Serum osmolality significantly decreased after treatment in all groups. pH significantly increased after treatment in each group, but in a comparison between groups, there were insignificant differences. Group I had the longest pediatric ICU stay. Conclusions Our patients continue to maintain normal or even have higher blood pressure levels with no hypotensive cases. The mean arterial blood pressure significantly decreased after treatment with intravenous fluids, especially in the group that received half NS. Rehydration with half NS results in decreased corrected sodium and more decrease in effective serum osmolality.